Meridional changes in the South Atlantic Subtropical Gyre during Heinrich Stadials - Tainã Marcos Lima Pinho (PANGAEA, 2021)
Subtropical ocean gyres play a key role in modulating the global climate system redistributing energy between low and high latitudes. A poleward displacement of the subtropical gyres has been observed over the last decades, but the lack of long-term monitoring data hinders an in-depth understanding of their dynamics. Paleoceanographic records offer the opportunity to identify meridional changes in the subtropical gyres and investigate their consequences to the climate system. Here we use the abundance of planktonic foraminiferal species Globorotalia truncatulinodes from a sediment core collected at the northernmost boundary of the South Atlantic Subtropical Gyre (SASG) to track changes in its meridional position. Our results show systematic decreases in the percentage of G. truncatulinoides during Heinrich Stadials (HS), indicating southward shifts of the northernmost boundary of the SASG.